2004
DOI: 10.1371/journal.pbio.0020211
|View full text |Cite
|
Sign up to set email alerts
|

Honeybee Odometry: Performance in Varying Natural Terrain

Abstract: Recent studies have shown that honeybees flying through short, narrow tunnels with visually textured walls perform waggle dances that indicate a much greater flight distance than that actually flown. These studies suggest that the bee's “odometer” is driven by the optic flow (image motion) that is experienced during flight. One might therefore expect that, when bees fly to a food source through a varying outdoor landscape, their waggle dances would depend upon the nature of the terrain experienced en route. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(93 citation statements)
references
References 17 publications
4
86
2
Order By: Relevance
“…Thus, when the trained bees are confronted with two sample stimuli, one at the training distance and the other at a different (unfamiliar) distance, they treat the stimulus at the familiar distance as the ''true'' sample stimulus and deem the other stimulus to be irrelevant. Recent work has shown that bees estimate distance flown in terms of the image motion that they experience en route (34)(35)(36)(37)(38)(39). In our experiments, however, the walls and floor of the tunnel were devoid of any visual texture, thus precluding accurate measurement of image motion.…”
Section: Discussionmentioning
confidence: 87%
“…Thus, when the trained bees are confronted with two sample stimuli, one at the training distance and the other at a different (unfamiliar) distance, they treat the stimulus at the familiar distance as the ''true'' sample stimulus and deem the other stimulus to be irrelevant. Recent work has shown that bees estimate distance flown in terms of the image motion that they experience en route (34)(35)(36)(37)(38)(39). In our experiments, however, the walls and floor of the tunnel were devoid of any visual texture, thus precluding accurate measurement of image motion.…”
Section: Discussionmentioning
confidence: 87%
“…The length of the single waggle-runs increases with the distance flown to reach the source, and their angles relative to gravity correlate with the direction of the foraging flights relative to the sun's azimuth in the field and sun-linked patterns of polarized skylight. Thus, by encoding the visually measured distance (Esch and Burns, 1995;Srinivasan et al, 2000a;Tautz et al, 2004) and the direction toward the goal, the waggle dance allows colony members to share information about the distance and direction toward a desirable goal (von Frisch, 1967;Seeley, 1995;Dyer, 2002). Although Karl von Frisch used the term ''dance language,' ' Premack and Premack (1983) correctly stated that the honeybee dances should not be called a language, based on the argument that there is no evidence that the bees can judge whether their dances conform to anything in their surroundings.…”
Section: Communicationmentioning
confidence: 99%
“…Thus, one might ask whether the waggle dance encodes spatial information provided only by the actual flight path. The role of landmarks so far has been considered only in the context of resetting (Srinivasan et al, 2000b) or calibrating the odometer (Tautz et al, 2004) but not in the communicative process. The detour experiments by von Frisch suggest that the directional component reported in the waggle dance may also be derived from stored path integration coordinates of visually defined locations (landmarks).…”
Section: Communicationmentioning
confidence: 99%
“…They were rescued from drowning only when the water surface was rippled or when a slatted bridge was placed on the water surface to provide sufficient contrast (Heran & Lindauer, 1963). Recent studies on bees trained to fly across a lake did not quite confirm these early results (Tautz et al, 2004), but the (large) lake may not have been as ripple-free as the (small) flooded quarry used in the original experiments. A featureless expanse of water no longer provides the animal's eye with any contrasting features, and the OF sensor will no longer respond.…”
Section: Flying Over Mirror-smooth Watermentioning
confidence: 97%